Activation of CXCL12/CXCR4 renders colorectal cancer cells less sensitive to radiotherapy via up-regulating the expression of survivin. Issue 4 (February 2017) - Wang, Dawei; Jiao, Chengbin; Zhu, Yanli; Liang, Deshen; Zao, Ming; Meng, Xiangyu; Gao, Jianwei; He, Yunlong; Liu, Weixin; Hou, Jie; Zhong, Zhaohua; Cheng, Zhuoxin
Colorectal cancer is the most common malignancy of the gastrointestinal tract. Surgical treatment combined with radiotherapy is the main treatment course for colorectal cancer; nevertheless, radio-resistance is commonly encountered during the treatment course and seriously influences the therapeutic efficacy. We tested the hypothesis that the CXCL12/CXCR4 axis is closely related to radiotherapy sensitivity in colorectal cancer cells. Here, we found that the decrease in cell viability and the increase in cell death induced by radiotherapy were attenuated by CXCL12 treatment, and the inhibition of CXCR4 promoted colorectal cancer cells to be more sensitive to radiotherapy. We also examined the critical roles of CXCL12/CXCR4 in cell survival and found that radiotherapy induced Bax expression and facilitated the activity of caspase-3 and caspase-9, which were reversed by CXCL12 treatment. Cell apoptosis was enhanced by the inhibition of CXCR4 under radiotherapy conditions. Furthermore, treatment with CXCL12 resulted in an increased expression of survivin, and the inhibitory roles of CXCL12 in radiotherapy-induced apoptosis were mitigated by survivin knockdown. These results indicate that CXCL12/CXCR4 protects colorectal cancer cells against radiotherapy via survivin, implying an important underlying mechanism of resistance to radiotherapy during colorectal cancer therapy.